Corpo e percepções no espectro autista. - Freitas, Ana Beatriz Machado de (2015)
This thesis understands that people with sensory impairments - including people with autism spectrum disorder - perceive the world in a qualitatively different way. However, the knowledge and the relevance of the perceptual dimension are little highlighted in the education area, even in studies and pedagogical training concerning Special Education. This study aims at investigating insights related to the autistic spectrum, primarily from the autistic people s perspective, that is, through living experience. This is a bibliographic review comprising four chapters. The first chapter discusses the pecial education presenting ideas on human development typically found in this field as well as their relevance according to L.S. Vygotsky s defectology principles. We learned that little emphasis is placed on its corporeal nature extrapolating its organic property. The second chapter focuses on studies about the perception over sensorial alterations or deficiencies in light of Maurice Merleau-Ponty s phenomenology references, to whom the body is intrinsically linked to the phenomenon of perception. The third chapter describes the autistic spectrum in scientific literature: clashing ideas regarding the (in)determinations in etiology and intervention alternatives. We contemplate the possibility of reading such spectrum from a phenomenological outlook. The fourth chapter centers around testimonies from people with autism spectrum disorder, mostly those stemming from Temple Grandin s biography regarding corporeal descriptions of perception. Two sub-themes surface: sensorial pathways and the body; corporeality and thinking. The testimonies related to these sub-themes are analyzed in light of the phenomenological perspective, with special attention to Merleau-Ponty s work, which corroborates our study. Our study, methodologically speaking, is faithful to the phenomenology principles in an attempt to understand the phenomenon from its manifestation bringing about endless issues regarding unreflected aspects, and, thus, enabling theory- based discussion that leads to its proposed essence. The present study highlights the dimension of one s own body as a key element to understand the perception of the autistic spectrum as well as its possibilities - impossibilities towards the world. Body s self-organization problems, i.e., concerning the body schema (as a unit) which expresses itself as meaning, intention, aesthetics and communication a difficulty intensified by asynchrony among sensory pathways - affects the body s inhabitation of the world, the perception - reading of this same unit in the others and in living situations. Therefore, it affects the quality of the interactions.